Al-Qur'an Sebagai Inspirasi Kemajuan Sains Dan Teknologi Dalam Peradaban Islam Abad Pertengahan - Rian Antoni; Suheri; Irfan Anshori (Al-Mudarris, 2025)
This research aims to analyze the role of the Qur'an as a source of inspiration in the scientific and technological advancement of medieval Islamic civilization through the study of the literature contributed by Muslim scientists in the golden era. The research method uses a qualitative approach with a literature study technique that analyzes the academic literature for the 2020-2025 period through inductive and comparative thematic analysis. The main findings of this study show that the integration of the kauniyyah verses of the Qur'an, Islamic scientific epistemology, and the heritage of Muslim scientists forms a holistic science paradigm, ethical, and relevant for the development of contemporary science and technology. The results of the study show that the Qur'an plays an important role as a source of inspiration in the development of science by combining observation of nature, rational thinking, and spiritual values. The study of kauniyyah verses shows that they encourage the birth of a comprehensive scientific way of thinking, as seen in the works of Muslim scholars such as Al-Khawarizmi, Ibn Sina, and Al-Razi. The study also found that references to the Qur'an were related to the rise of creativity and scientific innovation during the heyday of Islam. The model developed shows that the combination of spiritual values and scientific approaches results in a scientific tradition that is not only scientifically advanced, but also ethical and relevant to the development of science in the modern era.